Knowledge, attitude and practice regarding Type 2 diabetes mellitus among outpatients in a health center in East-Coast of Peninsular Malaysia - Mat Salleh, Rawaida; A. Rahman, Nor Azlina; Haque, Mainul (2019)
Introduction: Type 2 diabetes mellitus (T2DM) is becoming a global epidemic and a threat to the world population. Methods: This cross-sectional study was carried out to assess the knowledge, attitude, and practice (KAP) regarding T2DM among outpatients of a health center in East-Cost of Peninsular Malaysia. A total of 104 participants aged above 18 years were selected using purposive sampling by the researcher to answer an interviewer-guided questionnaire. The total scores for each KAP were computed to find the associations using SPSS. Results: There were significant correlations between knowledge and practice (r=0.481, p<0.001) and between age of participants with knowledge (r=0.562, p<0.001) and practice regarding T2DM (r=0.607, p<0.001). Besides, there was also a significant difference in terms of knowledge and practice regarding T2DM between different sexes and education levels. However, while making a comparison between Malays and other races, the significant difference was only found for practice regarding T2DM. The attitude was found to be similar in all groups. T2DM can be prevented by having accurate knowledge, adopting a positive attitude and practicing a healthy lifestyle. Conclusion: Therefore, policies and campaigns which may change people’s knowledge, attitudes, and practices for preventing T2DM should be properly formulated and implemented to tackle this health issue.